2015
DOI: 10.7554/elife.09771
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cell-free forward engineering of novel genetic ring oscillators

Abstract: While complex dynamic biological networks control gene expression in all living organisms, the forward engineering of comparable synthetic networks remains challenging. The current paradigm of characterizing synthetic networks in cells results in lengthy design-build-test cycles, minimal data collection, and poor quantitative characterization. Cell-free systems are appealing alternative environments, but it remains questionable whether biological networks behave similarly in cell-free systems and in cells. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
225
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(229 citation statements)
references
References 37 publications
(82 reference statements)
4
225
0
Order By: Relevance
“…Indeed, our discovery-centered cell-free approach sets the stage for high-throughput experimentation in a cell-free environment, where design–build–test iterations can be performed without the need to reengineer organisms, DNA for pathway enzymes is directly input with plasmid refactoring, and substrates and cofactors needed for secondary metabolism can be controlled and maintained at defined concentrations. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, our discovery-centered cell-free approach sets the stage for high-throughput experimentation in a cell-free environment, where design–build–test iterations can be performed without the need to reengineer organisms, DNA for pathway enzymes is directly input with plasmid refactoring, and substrates and cofactors needed for secondary metabolism can be controlled and maintained at defined concentrations. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Synthetic negative feedback loops, together with many other synthetic biology parts, such as the toggle switch and the repressilator, have been successfully reconstructed in cell-free systems [92,93]. Because experimental results have suggested that circuit performance in a cell-free system highly resembles its in-cell counterpart [91], cell-free systems can potentially serve as a rapid controller prototyping platform, similar to a wind tunnel for fluid dynamics, to investigate more sophisticated in vivo control strategies.…”
Section: ð4:1þmentioning
confidence: 99%
“…Finally, cell-free systems, where circuits are studied in cell extracts in vitro, provide appealing testing platforms to accelerate synthetic circuits prototyping, and to deepen our understanding of natural systems [90,91] by removing issues such as cellular context dependence, noise and cell heterogeneity, and cell growth. Synthetic negative feedback loops, together with many other synthetic biology parts, such as the toggle switch and the repressilator, have been successfully reconstructed in cell-free systems [92,93].…”
Section: ð4:1þmentioning
confidence: 99%
“…More recent work has addressed some of these limitations by improving the system in various ways (e.g. Stricker et al, 2008;Hussain et al, 2014;Niederholtmeyer et al, 2015). Some of these have been particularly useful in highlighting features that can make great differences to the precision of systems, some of which might be counter-intuitive.…”
Section: Box 1 Glossarymentioning
confidence: 99%